Analysis of stress concentration factor in bolted joint using finite element method - Khaleed Hussain, M. T.; Samad, Zahurin; Suhaib, S.; Uthman, A. R.; Jagirdar, S. A.; Badruddin, Irfan Anjum; Mallíck, Zulquernain; Khan, Zahid Akhtar; Abdul Quadir, Ghulam (University of Malaya, 2009)
Link to publisher's homepage at http://mechanical.eng.um.edu.my/